Akomodacja składniowa w obrębie grup imiennych z liczebnikiem głównym w średniowiecznej polszczyźnie - Słoboda, Agnieszka (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
This article aims at providing a description of nominal groups with the cardinal number in which a fluctuation in syntactic accommodation within the relations with the remaining elements of the group, i.e. adjectives and pronouns, occurs. In a separate evaluation – on account of idiosyncratic morphological and syntactic properties – groups with the numeral "dwa" (two) and with numerals with the paradigms of the nominal declension of the type "pięć" (five) are discussed. With the instance of groups with the numeral "dwa", the reason for fluctuations is not only the gradual disappearance of the dual form, but also the influence of Latin, in which this category receded very early. With numerals of the type "pięć", a gradual switch from the syntax subordinate to the numeral to the syntax subordinate to the superordinate noun in the nominal group is observable. This process was effected by a change in the syntactic function of the numeral and its gradual adjectivization.
Syntactic accommodation within nominal groups with the cardinal number in medieval Polish language
Keywords: liczebnik; składnia; akomodacja; grupa nominalna; średniowiecze